Demand for Organic Farming Technology and Roadmap for Technology Development - 김창길 (KREI, 2013)
Organic farming is a method of agricultural chemical․chemical fertilizer-free organic cultivation to produce agricultural products and to supply the produced agricultural products to consumers. As more organic agricultural products are predicted to be produced thanks to the spreading wellbeing trend of consumers and government’s support policy, further development of organic farming technology is needed. Therefore, it is very important to identify the demands for organic farming technology, and to suggest a needed roadmap for developing technology, for the mid- and long-term agricultural policy. The analysis of demands for organic farming technology for farmers in each field reveals high demands for using microorganisms and soil improvers in the field of soil and nutrient management technology. The field of weed control technology showed high demands for developing naturally decomposed vinyl products. The field of harmful insect control technology showed high demands for using organic materials, microorganisms and eelworms. The field of diseases control technology showed high demands for using natural materials and food, for example, egg yolk oil, vinegar, and pyroligneous liquid. Organic farming experts said the highest priority of 0.219 for the technology of recycling crop cultivation and livestock resources including compost, liquid fertilizers and organic fertilizers in the investigation of applying the AHP method to analyze the priority of developing organic farming technology. The highest priority is followed by 0.125 for bio-agricultural chemical, and then 0.119 for the technology of cultivating green manure crops. It is necessary to develop a key project for each field of higher priority to input research funds for continuous technology development. The development roadmap for each field is suggested in consideration of priorities of developing organic farming technology. In particular, required is to build a system for recycling crop cultivation and livestock farming by developing technology for organic crop cultivation and livestock recycling; a system for controlling eco-friendly organic farming soil and nutrients by developing technology for controlling organic soil and nutrients; a system for eco-friendly weed control by developing organic weed control technology; an eco-friendly system for controlling organic diseases and harmful insects by developing organic disease and harmful insect control technology; an eco-friendly system for organic seeds and seedlings by developing organic seed and seedling technology. It is essential to establish a technology development direction and the strategy for performance of each field for the R&D investment plan (2013-2022) in the agricultural sector. Because it is predicted that organic farming will continue to develop as a field of future growth in agriculture, it is necessary to expand R&D investment in related technology development. It is necessary to adopt farmers’ and experts’ opinion to continue technology development to respond to demands in order to supply safe agricultural products to consumers by means of steady development of organic farming.